2020
DOI: 10.1055/s-0040-1721690
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Maternal and Neonatal Serum Lipid Profile and Their Impact on Birth Weight

Abstract: Objective Maternal malnutrition with disturbed lipid metabolism during pregnancy may affect the fetal lipid profile. We aimed to detect the relation between maternal and neonatal serum lipid profile, as well as to detect the serum lipid profile difference between small for gestational age (SGA) infants and appropriate for gestational age (AGA) infants to disclose the impact of maternal malnutrition on birth weight. Study Design A cross-sectional study was conducted on 150 pregnant women coming to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…In addition, our study observed that increased TG levels in the first trimester were correlated with elevated risks of macrosomia, which was rarely studied previously. A negative association between TG levels and SGA was also found in the current study, which is consistent with several previous studies ( 12 , 40 ). In a word, TG exhibited a significant relationship with birth weight and adverse birth outcomes, indicating that TG might play an important role in fetal growth.…”
Section: Discussionsupporting
confidence: 94%
“…In addition, our study observed that increased TG levels in the first trimester were correlated with elevated risks of macrosomia, which was rarely studied previously. A negative association between TG levels and SGA was also found in the current study, which is consistent with several previous studies ( 12 , 40 ). In a word, TG exhibited a significant relationship with birth weight and adverse birth outcomes, indicating that TG might play an important role in fetal growth.…”
Section: Discussionsupporting
confidence: 94%
“…They differed in sample size, ranging from 119 to 5,282. Four of these included publications were cohort studies ( 12 14 , 17 ), two were case-control studies ( 15 , 18 ) and two were cross-sectional studies ( 11 , 16 ). They were conducted in different countries, Netherlands ( 12 ), China ( 13 ), Turkey ( 16 ), Japan ( 18 ), Korea ( 14 ), Canada ( 15 ), German ( 17 ) and Egypt ( 11 ) separately.…”
Section: Resultsmentioning
confidence: 99%
“…Each item was scored "0" if answered "No" or "Unclear"; when it was answered "Yes, " the item was scored "1." We considered articles as having low quality (scores of 0-3), moderate quality (scores of 4-7) or high quality (scores of [8][9][10][11].…”
Section: Study Selection Data Collection and Data Itemsmentioning
confidence: 99%
See 2 more Smart Citations